FE simulation on fatigue failure due to cracks initiated at corrosion zone - Chong, Kah Leong (Nanyang Technological University, 2024)
Deep-sea pipelines are subject to large plastic strains due to reeling installation methods.. While these pipelines can withstand small cracks generated during installation, cyclic loading in the deep-sea environment causes cracks to grow and merge, leading to fatigue failure. The corrosion zone in deep-sea pipelines is particularly susceptible to crack initiation and propagation. This study investigates the fatigue behaviour of 3D interacting cracks in the corrosion zone of deep-sea pipelines. The finite element method (FEM) is used to model the fatigue behaviour of these interacting cracks under cyclic loading. The parameters affecting the fatigue behaviour of deep-sea pipelines in the corrosion zone have been thoroughly studied.